Development of Vancomycin-Loaded Polysaccharide-Based Hydrogel Wound Dressings: In Vitro and In Vivo Evaluation - Mali, Kailas K. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of this study was to develop and evaluate carboxymethylcellulose (CMC) and tamarind gum (TG)-based citric acid cross-linked vancomycin-loaded hydrogel dressing for wound healing. Materials and Methods: CMC and TG are known for its biocompatibility and biodegradability and hence selected for preparation of hydrogel dressings. The hydrogel films were characterized by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, solid-state 13C-nuclear magnetic resonance (13C-NMR) spectroscopy, differential scanning calorimeter (DSC), and scanning electron microscopy (SEM). The prepared hydrogel films were evaluated for the carboxyl content and equilibrium swelling ratio. Vancomycin hydrochloride was loaded into hydrogels films and drug release was studied in the phosphate buffer pH 7.4. The hemolysis assay was used to study the biocompatibility of hydrogel films. The wound healing activity of optimized hydrogel film was studied in the albino mice of either sex. Results and Discussion: The results of ATR-FTIR, solid-state 13C-NMR, DSC, and SEM confirmed the formation of citric acid cross-linked hydrogel films. The total carboxyl content of hydrogel film was found to be increased when polymer ratio and amount of cross-linker was increased. The prepared hydrogel dressing showed pH-dependent swelling and swelling was decreased significantly with increase in the concentration of TG and cross-linker. Optimized hydrogel dressing batch HD1 exhibited highest drug loading with non-Fickian drug release. Hydrogel dressings were found to be hemocompatible and exhibited wound healing activity in mice. Conclusion: It can be concluded that the citric acid cross-linked polysaccharide-based hydrogel dressings have potential application in the development of topical drug delivery systems for treatment of the wound.